Thermally and Stress Induced Phase Transformations and Reversibility in Shape Memory Alloys - Adiguzel, O. (Springer, 2020)
Shape memory alloys take place in class of functional materials due to the sensitivity to the external conditions and memory behavior and shape changes are governed by successive thermally and stress induced martensitic transformations in crystallographic level. Shape memory effect is performed on cooling by means of thermal induced martensitic transformation and stressing in the low temperature product phase region by means of stress induced martensitic transformation. Following these processes, shape memory materials cycle between original and deformed shapes on heating and cooling, by means of reverse and forward thermal induced transformations. Mechanical memory is performed only mechanically in a constant temperature in the parent phase region, on stressing and releasing. This behavior is called superelasticity, which exhibits classical elastic material behavior, but stressing and releasing paths follow different paths in stress-strain diagrams. The hysteresis loop refers to the energy dissipation, and these alloys are mainly used as deformation absorbent materials in the buildings, due to the absorbance of strain energy during any disaster or earthquake. Thermal induced martensite occurs as twinned martensites by means of lattice invariant shears on close packed planes of parent structure, and the twinned martensites turn into detwinned structures with deformation by means of stress induced transformation. In the superelasticity, ordered parent phase structures turn into detwinned structure by means of stress induced transformation, and crystal structure cycles between these structures on stressing and releasing. Copper based alloys exhibit this property in metastable beta-phase region, which has bcc based structures at high temperature parent phase field. Crystallographic studies; x-ray and electron diffraction studies performed two copper based CuZnAl and CuAlMn alloys reveal that diffraction profiles exhibit super lattice reflections, and crystal structures change with long term aging in martensitic condition. This result refers to the rearrangement of atoms in diffusive manner. © 2020, Springer Nature B.V.
Keywords: Martensitic Transformations; Reversibility; Shape memory effect; Superelasticity; Thermal memory; Thermoelasticity; Twinning and detwinning